The Applications of Plasma Techniques II - Jasiński, Mariusz (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The collection of articles discussed above covers various types of discharges and various processes. The discharges presented include, for example, microwave, spark, glow or surface discharges. The characterizations of the sources of these discharges, the parameters of the generated plasmas as well as the applications of these plasmas are discussed. The applications include, for example, the synthesis of nanoparticles or the treatment of skin cancer cells. I hope that the presented articles will be valuable for readers representing the world of science, medicine and technology.